A sex paradox in clinical outcomes following complex percutaneous coronary intervention. (15th April 2021) - Nicolas, Johny; Claessen, Bimmer E.; Cao, Davide; Chiarito, Mauro; Sartori, Samantha; Qiu, Hanbo; Goel, Ridhima; Nardin, Matteo; Roumeliotis, Anastasios; Vogel, Birgit; Turfah, Ali; Chandiramani, Rishi; et al.
Abstract: Background: Although the number of complex percutaneous coronary intervention (CPCI) procedures is increasing, data regarding sex-related outcomes following CPCI are scarce. Methods: We retrospectively analyzed data of patients enrolled in a single-center registry between 2009 and 2017. Patients were divided into two groups (CPCI and non-CPCI) stratified by sex. CPCI was defined as any PCI procedure with ≥1 of the following characteristics: ≥3 target vessels/lesions, ≥3 stents implanted, bifurcation with ≥2 stents, stent length > 60 mm, or chronic total occlusion. The primary outcome was major adverse cardiac events (MACE), a composite of all-cause death, myocardial infarction (MI), and target vessel revascularization, at oneon-year follow-up. Results: Among 20, 419 patients, 5004 (24.5%) underwent CPCI of whom 25.6% ( n = 1281) women and 74.4% ( n = 3723) men. Women presented with more comorbidities yet less complex coronary anatomy than men (syntax score: 19.5 ± 10.3 vs. 20.6 ± 10.7, p = 0.009). Moreover, women were more likely to fulfill a single rather than multiple CPCI criteria. At one year, a higher rate of MACE occurred in women (14.0% vs. 11.6%, p = 0.02). After multivariable adjustment for confounders, the risk of MACE at one year was similar among both sexes (HR:1.04, 95% CI [0.85–1.26], p = 0.71), without significant interaction between the complexity of the procedure and sex (p-interaction = 0.96). Nonetheless, the risk of MI was significantly higher in women than men undergoing CPCI (HR:1.63, 95% CI [1.12–2.38], p = 0.01). Conclusions: Despite presenting with less challenging lesions than men, women had a higher rate of MI at one year following CPCI, even after adjusting for potential confounders. Graphical abstract: Unlabelled Image Highlights: Women represent one fourth of patients undergoing complex PCI. Women have more comorbidities yet less complex coronary anatomy than men. Compared with men, women have a worse prognosis following complex PCI.